1985
DOI: 10.1159/000287865
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Studies on Anorexia nervosa in Japan: Detailed Clinical Data on 1,011 Patients

Abstract: Statistical studies on anorexia nervosa in Japan were carried out by our research group. Questionnaires were sent to physicians at 1,030 representative institutions throughout Japan and data were collected from 315 institutions. The total number of patients with anorexia nervosa in 1981 was 940 outpatients and 372 inpatients. The number of patients in 1981 was twice as high as in 1976. Detailed data on 1,011 patients were investigated. As most of the patients had certain endocrinological abnormalities which im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 3 publications
(4 reference statements)
4
28
0
Order By: Relevance
“…The earliest studies of eating disorders in Japan suggested that both anorexia nervosa (AN) and bulimia nervosa (BN) were less common than in Western countries (Inaba & Takahashi, 1989;Suematsu, Ishikawa, Kuboki, & Ito, 1985;Kiriike et al, 1988). The predominant explanation for the apparent difference was rooted in sociocultural theories, which held that eating disorders are culture-bound syndromes (Striegel-Moore, Silberstein, & Rodin, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest studies of eating disorders in Japan suggested that both anorexia nervosa (AN) and bulimia nervosa (BN) were less common than in Western countries (Inaba & Takahashi, 1989;Suematsu, Ishikawa, Kuboki, & Ito, 1985;Kiriike et al, 1988). The predominant explanation for the apparent difference was rooted in sociocultural theories, which held that eating disorders are culture-bound syndromes (Striegel-Moore, Silberstein, & Rodin, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…These changes are associated with at least a sixfold increase in eating disorders over the past 25 years (Kiriike & Nagata, 1997;Kiriike et al, 1988;Nadaoka et al, 1996;Suematsu et al, 1985;Takagi, 1990). Moreover, from adolescence through adulthood, the presence of extreme dysregulation in eating and dieting among Japanese women has been documented at rates comparable to the rates among their North American counterparts and at rates that raise public health concerns (Koseisho, 1993;Maruyama et al, 1993;Mukai, Crago, & Shisslak, 1994;Takeuchi et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although Ja pan is not a Western country and the preva lence of anorexia nervosa is not the same as in Europe and North America [19,29], the coun try is highly industrialized and, especially in recent years, has adopted the cultural empha sis on slimness [19]. Japanese patients with anorexia nervosa were demonstrated to have weight phobia [29]. The patients seem similar not to those in Hong Kong or India, but rather to Western countries [8],…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for the diagnosis of anorexia nervosa [1] were defined as follows: (1) a loss of more than 20% of standard body weight; (2) a history of weight loss for more than 3 months; (3) age of onset before 30 years; (4) female; (5) amenorrhea; (6) eating disorders; (7) desire to reduce body weight (disturbance of body image); (8) hyperactivity; (9) denial of illness, and ( 10) no known physical illness or psychiatric disorder such as schizophrenia or depression.…”
Section: Methodsmentioning
confidence: 99%